A homocysteine-selective fluorescent probe for cell imaging based on substitution-rearrangement process. (November 2022) - Yang, Linlin; Gu, Pengli; Li, Beining; Li, Junwan; Fu, Aoxiang; Gong, Xianyu; Huang, Yanmei; Xie, Lixia; Ji, Liguo; Ma, Nana; Li, Lili; He, Guangjie
Abstract: Biothiols play an important role in cell protein metabolism and signal transduction, especially Hcy was considered as a new risk factor closely related to many diseases. However, there remain some limitations in selectively detecting Hcy due to its structural similarity to Cys. It is urgent for us to develop a novel indicator to study the pathological process of Hcy. Herein, we constructed a new fluorescent probe TCF-SBD composed of tricyanofuran fluorophore and SBD reaction site for detecting Hcy. The probe TCF-SBD exhibited a strong yellow emission response to Hcy in an "off-on" manner, and showed good selectivity for Hcy over Cys and GSH. The sensing mechanism was confirmed by HPLC, NMR titration and DFT studies. The probe was sensitive to the detection of Hcy with LOD low to 0.23 μM. The powerful probe TCF-SBD succeeded in real-time and selectively visualizing Hcy in living cells. Graphical abstract: Image 1 Highlights: Fluorescence probe based on substitution-rearrangement process was synthesized for selective detection of Hcy. The probe displayed high selective and sensitive for Hcy (detection limit is 0.23 μM). The probe was applied for fluorescence imaging of exogenous Hcy in living cells.